Pharmacokinetic and Myocardial Enzyme Profiles of Two Administration Routes of Epirubicin in Breast Cancer Patients - Yang, R.-X.; Ren, H.-X.; Zhuang, L.; Gao, C.-L.; Dong, C.; Luo, C.-X; Wang, X.-N.; Feng, E.-F.; He, J.-C. (Arzneimittelforschung, 2012)
To evaluate the changes in myocardial enzymes and plasma epirubicin concentration following administration by micro-pump (MP) and intravenous drip (ID) in breast cancer patients.11 self-controlled breast cancer patients were recruited for a trial with epirubicin administration by MP for 48 h and by ID for 1 h during 2 cycles of treatment. Plasma concentration of epirubicin at different time points was determined using LC-MS/MS. The levels of myocardial enzymes before and after chemotherapy were compared. Another group of patients receiving epirubicin by ID (n=4) or MP (n=9) were monitored for 4 months.8 patients completed the self-controlled study. The peak concentration of epirubicin in the MP group and the ID group were 21.84±18.85 ng/mL and 294.80±225.54 ng/mL, respectively. The MP group had a longer duration (54~60 h) of plasma concentration of epirubicin not less than 10 ng/mL than that of the ID group (8~14 h). There was significant difference for the alteration of myocardial enzymes before and after chemotherapy (p<0.05) in the ID group, whereas the MP group showed no significant difference (p>0.05). The increased range of myocardial enzymes after chemotherapy in the ID group was larger than that of the MP group and the difference was significant (p<0.05). There is an increased cardiotoxicity in patients receiving epirubicin by ID during the 4-month trial.Administration of epirubicin by MP maintained an effective drug concentration for a longer period of time than by ID. The higher peak plasma concentration observed following epirubicin administration by ID may lead to cardiac toxicity.
Keywords: epirubicin; pharmacokinetics; micro-pump; intravenous drip; breast cancer